Revitalizing the HIV Response in Pakistan : A Systematic Review and Policy Recommendations - Beyrer, Chris; Singh, Sonal; Ambrosio, Marco; Semini, Iris (World Bank, Washington, DC, 2017)
Pakistan has made strides over the last decade in its Acquired Immunodeficiency Syndrome (AIDS) response, with active surveillance, considerable research, both governmental and non?governmental prevention and care activities, and treatment since 2005 to 2006. However, the Human Immunodeficiency Virus (HIV) prevalence among People Who Inject Drugs (PWID) has not declined, coverage of current prevention and treatment programs remains limited and the gains made to date are threatened by internal and external factors. This report attempts to review and synthesize available data on HIV in Pakistan and to use these data to suggest strategic priorities for the next phase of the HIV response in an effort to improve the allocative efficiency of resources and effective and efficient implementation of the response. This report presents an integrated model for HIV services delivery that depicts a continuum of care from prevention outreach to treatment with a focus on evidence based interventions and strong linkages. It describes three potential models for Volunteer Counseling and Testing (VCT) services for most at risk populations that increase outreach and engagement with PWID, hijra communities, and Male Sex Workers (MSWs), and their clients. It also places heavy emphasis on evidence based approaches to prevention including expanding treatment for High Risk Groups (HRGs) and improving the linkages for HIV positive and HIV negative PWID for drug treatment services, such as Methadone Maintenance Therapy (MMT), and outlines the steps for an evidenced based, effective and efficient policy response at a time of shrinking resources for HIV in overall low prevalence settings. This report is organized as follows: chapter one gives introduction; chapter two presents epidemiology methods; chapter three gives country context; chapter four presents status of HIV epidemic; chapter five gives summary of key findings; chapter six deals with systems response to HIV and AIDS in Pakistan; chapter seven gives key policy recommendations; and chapter eight gives conclusion.